In Utero Nutritional Manipulation Provokes Dysregulated Adipocytokines Production in F1 Offspring in Rats. (20th April 2016) - Hanafi, Mervat Y.; Saad, Mohamed I.; Abdelkhalek, Taha M.; Saleh, Moustafa M.; Kamel, Maher A.
Abstract : Background . Intrauterine environment plays a pivotal role in the origin of fatal diseases such as diabetes. Diabetes and obesity are associated with low-grade inflammatory state and dysregulated adipokines production. This study aims to investigate the effect of maternal obesity and malnutrition on adipokines production (adiponectin, leptin, and TNF- α ) in F1 offspring in rats. Materials and Methods . Wistar rats were allocated in groups: F1 offspring of control mothers under control diet (CF1-CD) and under high-fat diet (CF1-HCD), F1 offspring of obese mothers under CD (OF1-CD) and under HCD (OF1-HCD), and F1 offspring of malnourished mothers under CD (MF1-CD) and under HCD (MF1-HCD). Every 5 weeks postnatally, blood samples were obtained for biochemical analysis. Results . At the end of the 30-week follow-up, OF1-HCD and MF1-HCD exhibited hyperinsulinemia, moderate dyslipidemia, insulin resistance, and impaired glucose homeostasis compared to CF1-CD and CF1-HCD. OF1-HCD and MF1-HCD demonstrated low serum levels of adiponectin and high levels of leptin compared to CF1-CD and CF1-HCD. OF1-CD, OF1-HCD, and MF1-HCD had elevated serum levels of TNF- α compared to CF1-CD and CF1-HCD (p < 0.05 ). Conclusion . Maternal nutritional manipulation predisposes the offspring to development of insulin resistance in their adult life, probably via instigating dysregulated adipokines production.